Bioremediation Of Endosulfan By Bacteria Isolated From The Agricultural Fields - SUMIT KUMAR (International Journal of Pharma and Bio Sciences, 2011)
In the present study, endosulfan degrading capability of four bacterial monocultures (RCE-2, GCE-4, GCE-5 and JCE-4) and two bacterial mixed-cultures (GCE345 and GCC134) was investigated in terms of treatment duration and culture volume, using soil slurry medium. Among the bacterial mono-cultures, JCE-4 was found to be most efficient with 16, 33, 60 and 65% of endosulfan (α + β-isomers) degradation in 5, 10, 15 and 30 days of treatment, respectively. Out of two bacterial mixed-cultures, GCE345 was more efficient and resulted in 20, 39, 57 and 73% degradation of endosulfan (α + β-isomers) in 5, 10, 15 and 30 days of treatment, respectively. The fraction of endosulfan degraded was found to be higher with the increase in treatment duration till 30 days. The endosulfan degradation was also elevated by increasing the culture volume of respective bacterial cultures from 10% to 25% (v/v), for 10 days of treatment at room temperature.